Exploration and Analysis of Evolutions of Foreign Investment Law: Past, Present and Future - Janet Dine; Mohammad Arian (پژوهش‌نامه حقوق اسلامی, 2013)
In today’s world, there is no room for doubt that foreign investment isconsidered as one of the most noteworthy pillars of economic andsocial development which its governing law has undergone massivechanges during past periods. The current legal framework governingthe process of foreign investment has been under far-reachingevolution. Deep exploration and substantial analysis of the saidevolution will bring the fruit of enhanced vision, paving the way forproviding a roadmap for future regulation of foreign investment bothat national and international levels. In this context, some questionswill be posed as follows; under what factors or surroundingconditions, the legal system governing the process of foreigninvestment has been evolved in each period? Whether development ofrules in the field of foreign investment in different eras has matchedthe existing requirements? In current period, what is the targetedapproach for the regulation of foreign investment at internationallevel? Whether this approach can harness or remove the undesirableimpacts of foreign investment? In this paper, it has been attempted toevaluate and analyze the status of regulatory evolutions of foreigninvestment and to explain its future trends.